Swimming alone? Why linking flood risk perception and behavior requires more than "it's the individual, stupid". (14th July 2020) - Rufat, Samuel; Fekete, Alexander; Armaş, Iuliana; Hartmann, Thomas; Kuhlicke, Christian; Prior, Tim; Thaler, Thomas; Wisner, Ben
Abstract: A common assertion in discussions of flooding is that risk perception is critical and is linked to risk‐mitigating behavior. Furthermore, many assert that the adverse effects of floods could be reduced by changes in risk communication, thereby influencing risk perception to foster mitigating behavior. We argue that these assertions are based on quite questionable underlying assumptions: That stakeholders are generally aware of flood risk, that they have the capacity to engage in disaster risk reduction, and that their actions can be effective. The belief in and policies influenced by these three questionable assertions support, in turn, policies that shift responsibility for flood risk reduction onto individuals and homeowners, without regard for social and spatial justice issues. In contrast, we argue that context matters to understanding the complexity of the relation between flood risk perception and behavior, local power relations, and other constraints and opportunities that affect stakeholders. While the academic community has long played a pivotal role in supporting practical flood risk management, future research should take a more critical perspective on the underlying assumptions and focus on improving coordination across theories, methods, and variables, fostering comparative studies across disciplines, contexts, and scales. This article is categorized under: Engineering Water > Planning Water Human Water > Water as Imagined and Represented Science of Water > Water Extremes